2018
DOI: 10.3390/ijerph15061174
|View full text |Cite
|
Sign up to set email alerts
|

Cost-of-Illness and the Health-Related Quality of Life of Patients in the Dengue Fever Outbreak in Hanoi in 2017

Abstract: Dengue fever (DF) outbreaks occur intermittently in Vietnam, and the most recent epidemic happened in 2017. However, attempts to measure the burden of DF in relation to the quality of life and the cost of treatment for patients during an epidemic period are constrained. This study explored the health-related quality of life (HRQOL) and the cost of illness among patients with dengue fever in Vietnam. A cross-sectional study was conducted in Bach Mai Hospital from September to November 2017. The EuroQol-5 dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Dengue significantly reduces HRQOL beyond the febrile phase. Mobility, pain, and usual activities were the most affected domains, consistent with previous studies (8,12). The proportion of patients reporting problems remained stable among patients with persistent symptoms of dengue.…”
Section: Discussionsupporting
confidence: 89%
“…Dengue significantly reduces HRQOL beyond the febrile phase. Mobility, pain, and usual activities were the most affected domains, consistent with previous studies (8,12). The proportion of patients reporting problems remained stable among patients with persistent symptoms of dengue.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted by Jarab et al reported a moderately reduced HRQoL among patients with type 2 diabetes in Jordan. In this study, the total mean EQ‐5D score of osteoporosis is 0.62, which is lower than other medical conditions such as diabetes (total mean EQ‐5D score = 0.8), human immunodeficiency viruses (HIV) infection (total mean EQ‐5D score = 0.8), skin disease (total mean EQ‐5D = 0.73), respiratory disease (total mean EQ‐5D = 0.66) and dengue fever (EQ‐5D = 0.66) …”
Section: Discussionmentioning
confidence: 69%
“…In this study, the total mean EQ-5D score of osteoporosis is 0.62, which is lower than other medical conditions such as diabetes (total mean EQ-5D score = 0.8), [13] human immunodeficiency viruses (HIV) infection (total mean EQ-5D score = 0.8), [14] skin disease (total mean EQ-5D = 0.73), [15] respiratory disease (total mean EQ-5D = 0.66) [16] and dengue fever (EQ-5D = 0.66). [17] Earlier studies which have investigated the effect of vitamin D on daily activities and HRQoL have found controversial finding. Some of these studies reported that vitamin D had positive effect on HRQoL, [18] while others reported no effect.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the pathogenesis of AD is necessary before developing new therapeutics [29]. In recent years, advances in AD biomarker detection in the preclinical/prodromal phase of the disease indicate their effectiveness in reducing incidents related to AD [30][31][32][33][34]. Consumers in health settings with low resources were found to be highly sensitive to the cost of services.…”
Section: Discussionmentioning
confidence: 99%